MODERN ASPECTS OF HOMEOPATHIC MEDICINES STANDARDISATION - E. I. Sakanyan; N. S. Tereshina; M. N. Lyakina (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article describes the status of homeopathic medicines standardisation in the leading world pharmacopoeias. It reviews main requirements for raw materials of plant, animal, and mineral origin, which are used in the production of homeopathic medicines. It also considers requirements for homeopathic pharmaceutical substances, including technologies of obtaining homeopathic mother tinctures, homeopathic dilutions, triturations, etc., mono- and multi-component homeopathic medicines, as well as quality control of homeopathic substances and homeopathic medicines. The article analyses the nomenclature of homeopathic raw materials and homeopathic substances used by the leading world pharmacopoeias. It dwells upon the results of work devoted to the development of requirements for the following homeopathic dosage forms: homeopathic granules, homeopathic eye drops, homeopathic ointments, homeopathic infusions and decoctions,  homeopathic mother tinctures,  homeopathic solutions for injection,  homeopathic solutions and liquid dilutions,  homeopathic syrups, homeopathic mixtures,  homeopathic suppositories, homeopathic tablets, homeopathic triturations.  The article illustrates significant potential of using vibrational spectroscopy and Raman spectroscopy for the detection of distinctive features of homeopathic medicines at ultra-high dilutions. The article presents methodology for structuring pharmacopoeial standards for raw materials used in the production of pharmaceutical substances, for pharmaceutical substances that are used in homeopathic medicines, and for dosage forms, including specific aspects of production and standardisation of homeopathic medicines, which was implemented during preparation of draft monographs for the State Pharmacopoeia of the Russian Federation.